Efek penggunaan mikroorganisme lokal dalam amofer rumput kume terhadap kandungan bahan kering, bahan organik dan kecernaanya secara in vitro - Luminata, Fransiska; Hilakore, Maritje A.; Lazarus , Edwin J. L.; Lawa, Emma D. Wie (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aims to determine the effect of the use of local microorganism level (MOL) in the manufacture of dry kume grass amofer on the content of dry matter, organic matter, digestibility of dry matter and organic matter in vitro. The method used in this study was an experimental method using a completely randomized design (CRD) consisting of 4 treatments and 4 replications. The treatment applied was: P0 = Ammoniated dry kume grass + 5% putak flour + 5% sugar; P1= P0 + 40 ml MOL; P2= P0 + 80 ml MOL; P3= P0 + 120 ml MOL The variables measured were the contents of dry matter, organic matter, dry matter and organic matter digestibility. Data were analyzed using Analysis of variance (ANOVA) and continued with Duncan's multiple range test. The results of the statistical analysis showed that the treatments had a significant effect (P<0.05) on the dry matter contents, digestibility of the dry matter and organic matter in vitro. It was concluded that the use of local microorganism levels in the ammoniation of dry kume grass fermentation could increase dry and organic matter, dry and organic matter digestibility in vitro.